2013
DOI: 10.1111/pde.12089
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol and Infantile Hemangiomas Four Years Later: A Systematic Review

Abstract: To systematically review the literature evaluating efficacy and adverse events of propranolol treatment for infantile hemangiomas, we searched the MEDLINE and Cochrane databases for all studies examining the response of infantile hemangiomas (IHs) to propranolol published between June 12, 2008, and June 15, 2012. Forty-one studies with 1,264 patients were included; 74% of patients were female and approximately 30% had received other treatments before propranolol. Propranolol was initiated at a mean age of 6.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
206
0
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(232 citation statements)
references
References 57 publications
13
206
0
13
Order By: Relevance
“…159,161,180,181 In a systematic review of propranolol treatment of IH, there were 371 total adverse effects reported in 1189 patients. 182 Those most commonly reported were sleep disturbance (136 patients), acrocyanosis (61 patients), hypotension (39 patients, including 5 considered "symptomatic"), bradycardia (8 patients, including 1 considered symptomatic), and respiratory events including infections, wheezing, and stridor (35 patients).…”
Section: Management Of Ulcerated Ihsmentioning
confidence: 99%
“…159,161,180,181 In a systematic review of propranolol treatment of IH, there were 371 total adverse effects reported in 1189 patients. 182 Those most commonly reported were sleep disturbance (136 patients), acrocyanosis (61 patients), hypotension (39 patients, including 5 considered "symptomatic"), bradycardia (8 patients, including 1 considered symptomatic), and respiratory events including infections, wheezing, and stridor (35 patients).…”
Section: Management Of Ulcerated Ihsmentioning
confidence: 99%
“…We also note that other approaches to meta-analysis could be used but that our estimates of a high anticipated response to propranolol largely align with those in other reviews of propranolol. [38][39][40][41] The evidence base for IH treatment is limited by a small number of comparative studies including a limited number of participants. A growing number of studies address β-blockers, but current studies are limited by a general lack of long-term follow-up and analyses to explore differences in response among subgroups.…”
Section: Figurementioning
confidence: 99%
“…El propranolol reduce el tamaño del tumor y detiene su crecimiento. [65][66] Es eficaz en todas las fases de la evolución del HI, aun en la involutiva. Los pacientes requieren una evaluación cardiológica antes de comenzar el tratamiento.…”
Section: Betabloqueantesunclassified
“…Las otras posibles adversidades son leves y reversibles. 66 (Figuras 7 y 8 pretratamiento y postratamiento). Aún no hay consenso respecto de la duración del tratamiento.…”
Section: Betabloqueantesunclassified